Real-Time Pricing-Based Scheduling Strategy in Smart Grids: A Hierarchical Game Approach - Jie Yang; Guoshan Zhang; Kai Ma (Journal of Applied Mathematics)
This paper proposes a scheduling strategy based on real-time pricing in smart grids. A hierarchical game is employed to analyze the decision-making process of generators and consumers. We prove the existence and uniqueness of Nash equilibrium and utilize a backward induction method to obtain the generation and consumption strategies. Then, we propose two dynamic algorithms for the generators and consumers to search for the equilibrium in a distributed fashion. Simulation results demonstrate that the proposed scheduling strategy can match supply with demand and shift load away from peak time.